One-shot preparation of topologically chimeric nanofibers via a gradient supramolecular copolymerization - Yuichi Kitamoto (Nature Portfolio, 2019)
Supramolecular polymers can form highly accessible polymeric nanomaterials. Here the authors report the facile preparation of supramolecular copolymers involving segregated secondary structures by cooling non-polar solutions containing two monomers that individually afford helically folded and linearly extended secondary structures.